Crystal and molecular structure of V-amylose complexed with butan-1-ol. (14th March 2022) - Le, Cong Anh Khanh; Mazeau, Karim; Nishiyama, Yoshiharu; Ogawa, Yu; Choisnard, Luc; Wouessidjewe, Denis; Putaux, Jean-Luc
Abstract: Chain-folded lamellar V-amylose single crystals were prepared by adding butan-1-ol to hot dilute aqueous solutions of native amylose. The base-plane electron and X-ray diffraction patterns recorded from hydrated specimens agreed with a P 21 21 21 space group and an orthorhombic unit cell. A molecular model resulting from an exhaustive search of helix position and restrained structure refinement against diffraction data was proposed. The unit cell contains 4 antiparallel left-handed 6-fold amylose single helices with 1 butan-1-ol molecule located inside each of the helical cavities. In addition, 4 butan-1-ol and 20 water molecules are distributed in the 4 interstitial spaces. The amylose helices form rows along the b -axis that are alternatively shifted by ± b /8 with respect to one another, which validates the geometrical model proposed by Helbert and Chanzy in 1994. Graphical abstract: Image 1 Highlights: Native amylose formed chain-folded lamellar co-crystals with butan-1-ol. Electron and X-ray diffraction data confirmed the orthorhombic unit cell. The possible packing of amylose helices and guest distribution were explored. Butan-1-ol molecules are located inside 6-fold amylose helices and in-between. The results validate the geometrical model proposed by Helbert and Chanzy.